MARCH9‐mediated ubiquitination regulates MHC I export from the TGN. Issue 9 (25th July 2017) - De Angelis Rigotti, Francesca; De Gassart, Aude; Pforr, Carina; Cano, Florencia; N'Guessan, Prudence; Combes, Alexis; Camossetto, Voahirana; Lehner, Paul J; Pierre, Philippe; Gatti, Evelina
Abstract : Given the heterogeneous nature of antigens, major histocompatibility complex class I (MHC I) intracellular transport intersects with multiple degradation pathways for efficient peptide loading and presentation to cytotoxic T cells. MHC I loading with peptides in the endoplasmic reticulum (ER) is a tightly regulated process, while post‐ER intracellular transport is considered to occur by default, leading to peptide‐bearing MHC I delivery to the plasma membrane. We show here that MHC I traffic is submitted to a previously uncharacterized sorting step at the trans Golgi network (TGN), dependent on the ubiquitination of its cytoplasmic tail lysine residues. MHC I ubiquitination is mediated by the E3 ligase membrane‐associated RING‐CH 9 (MARCH9) and allows MHC I access to Syntaxin 6‐positive endosomal compartments. We further show that MARCH9 can also target the human MHC I‐like lipid antigen‐presentation molecule CD1a. MARCH9 expression is modulated by microbial pattern exposure in dendritic cells (DCs), thus revealing the role of this ubiquitin E3 ligase in coordinating MHC I access to endosomes and DC activation for efficient antigen cross‐presentation.